PEMANFAATAN MEDIA INTERAKTIF BERBASIS APLIKASI CANVA DALAM PEMBELAJARAN PAI DI SMPN 1 STABAT KABUPATEN LANGKAT - Pranata Wijaya, Juwanda; Nurmawati (Rabbani: Jurnal Pendidikan Agama Islam, 2025)
Technology has evolved since ancient times, starting from basic reliance on natural forces. Over time, industrial technology has advanced, leading us into the modern era, including the current 5.0 era. This study focuses on the development of interactive learning media using Canva application by PAI teachers at SMPN 1 Stabat. The method used is descriptive qualitative with observations and interviews. The results show that the use of Canva increases learning efficiency and student motivation. However, the main challenges faced are mastering the technology, developing relevant content, and allocating time. Continuous training and support are needed to overcome these challenges and optimize the use of interactive media in education.